Punitiveness in Slovenia: A study of criminal justice students as future practitioners and decision-makers in the criminal justice system: Punitywność w Słowenii: badanie studentów wymiaru sprawiedliwości jako przyszłych praktyków i decydentów w systemie wymiaru sprawiedliwości (Archives of Criminology, 2022)
The paper focuses on the punitiveness and support of the death penalty among criminal justice students in Slovenia. First, a literature review on punishment and punitiveness, penal changes in Slovenia, and punitive attitudes among criminal justice students, is provided. In the second part of the paper, the results of the empirical study that took place among criminal justice students in Slovenia in 2019 are presented. Statistical analyses performed were based on a sample of 244 students at the Faculty of Criminal Justice and Security, University of Maribor. The findings highlighted retribution as the strongest predictor of students’ punitive attitudes, followed by support for harsh punishment. The majority of students (59.0%) were against the death penalty. The findings indicate that support for the death penalty among criminal justice students has been decreasing in recent years.